Proceedings of the 13th ACM SIGKDD International Conference on Knowledge Discovery and Data Mining 2007
DOI: 10.1145/1281192.1281268
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing semi-supervised clustering

Abstract: Semi-supervised clustering employs limited supervision in the form of labeled instances or pairwise instance constraints to aid unsupervised clustering and often significantly improves the clustering performance. Despite the vast amount of expert knowledge spent on this problem, most existing work is not designed for handling high-dimensional sparse data. This paper thus fills this crucial void by developing a Semi-supervised Clustering method based on spheRical K-mEans via fEature projectioN (SCREEN). Specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Ref. [51] presented a semi-supervised clustering method base on spherical K-Means via feature projection which is tailored for handling sparse high dimensional data. They first formulated constraint-guided feature projection then applied the constraint spherical K-Means algorithm to cluster data with reduced dimension.…”
Section: Recent Workmentioning
confidence: 99%
“…Ref. [51] presented a semi-supervised clustering method base on spherical K-Means via feature projection which is tailored for handling sparse high dimensional data. They first formulated constraint-guided feature projection then applied the constraint spherical K-Means algorithm to cluster data with reduced dimension.…”
Section: Recent Workmentioning
confidence: 99%
“…Moreover, Bair 8 evidences that traditional supervised classification methods are not useful when it is necessary to analyze a subset of labeled data. To solve the above mentioned problems of unsupervised clustering methods, several algorithms have been proposed to enhance clustering quality by employing supervision approaches 13,14 and, more precisely, by identifying the new class of semisupervised methods, that has recently become an important research topic 10,15‐18 . Semisupervised clustering is a variant of the traditional clustering paradigms.…”
Section: Introductionmentioning
confidence: 99%
“…In semisupervised clustering two different kinds of prior knowledge are considered: label information and pairwise constraints (or instance‐level constraints ) 18,23‐25 . Sometimes it is possible to distinguish between partial labels (a small subset of labeled instances) and instance‐level constraints (constraints characterizing pairs of data points) 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, she proposed a typical constrained kmeans algorithm based on these constraints. These advances led to many semi-supervised clustering methods based on pairwise constraints, such as constrained complete-link [4], constrained expectation-maximization (EM) [5], HMRFKmeans [6], MPCKmeans [7], kernel methods [8]- [13], matrix factorization-based methods [14], and constraint projection [15]- [18]. Kulis et al [8] reported a kernel algorithm to minimize a semi-supervised clustering objective function.…”
Section: Introductionmentioning
confidence: 99%